Hard times: an oral history of the great depression - Terkel,Studs (New yark, 1986)
In this (3z(Binvaluable record(3y (Bof one of the most dramatic periods in modern American history, Studs Terkel recaptures the Great Depression of the 1930s in all its complexity. Featuring a mosaic of memories from politicians, businessmen, artists, striking workers, and Okies, from those who were just kids to those who remember losing a fortune, Hard Times is not only a gold mine of information but a fascinating interplay of memory and fact, revealing how the 1929 stock market crash and its repercussions radically changed the lives of a generation. The voices that speak from the pages of this unique book are as timeless as the lessons they imparts
Keywords: Social history:Depressions:Oral history:Economic history